Determinasi Keputusan Menabung Gen Z pada Bank Syariah - Dinda Mutiara Putri Addini Aslam; Zubaidah Nasution (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2026)
The purpose of this study is to analyze the influence of Sharia Financial Literacy and Trust on Gen Z's Decision to Save in Sharia Banks. This study is a quantitative study using primary data. The population of this study is Generation Z in Surabaya who already have income or are working. The sampling technique used is purposive sampling, and 125 respondents who meet the criteria were obtained as research samples. Data was collected using a survey method through the distribution of questionnaires via g-form. This study used a Likert scale to measure variables. The data analysis techniques used were descriptive analysis and inferential analysis with the help of the Partial Least Square (PLS) program. The results showed that Islamic financial literacy and trust had a significant and positive effect on the decision to save in Islamic banks.